Percutaneous Biopsy and Drainage of the Pancreas - Redstone, Ellen A.; Li, Zhenteng (Seminars in Interventional Radiology, 2024)
Percutaneous biopsy and drainage of pancreatic lesions, though less frequent due to advancements in endoscopic techniques, remain vital skills for interventional radiologists. This review details the indications, options, approaches, and technical considerations for pancreatic biopsy and (peri)pancreatic fluid drainage by examining a comprehensive range of literature. The importance of a multidisciplinary approach is emphasized to ensure optimal patient care and outcomes, highlighting current best practices and recent advancements.
Keywords: pancreatic biopsy; pancreatic cancer; pancreas rejection; percutaneous drainage; interventional radiology